Implementation of MTTR and MTBF for Determining the Average Maintenance Interval of Press Machines at PT X - Rubayatun, Renno Ananda Saputra; Iriani (Yayasan Kita Menulis, 2026)
The independent internship program at PT X aims to apply Industrial Engineering concepts in a real industrial environment, particularly in the field of machine maintenance. This study focuses on analyzing the reliability of the press machine at Lane Kiln 2, which plays a crucial role in the ceramic production process. The methods used in this analysis are Mean Time Between Failures (MTBF) and Mean Time To Repair (MTTR) to evaluate the frequency of machine failures and the efficiency of repair time. Based on the data processing results presented in Chapter III, the MTBF value obtained is 703 minutes approximately 12 hours, and the availability of the press machine at Lane Kiln 2 is 93.64%. These results indicate that the machine availability level is relatively high and capable of supporting smooth production operations. However, the findings also suggest that although the repair process has been carried out effectively.